Pembuatan masker dan bilik disinfektan sebagai upaya membantu masyarakat terdampak covid-19 - Safi'i, Imam; Candra, Agata Iwan; Widodo, Silvi Rushanti; Santoso, Ariadi; Heryanto, Budi; Winarti, Eko; Rahmadi, Afif Nur (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The spread of Covid-19 in Indonesia has begun to increase from April 2020, this is because there are still many people who have not implemented the prevention of transmission such as one of them using masks. Observations made at crowded places such as traditional markets found that many people do not use masks due to the scarcity of masks in the market. The methods of making the masks and disinfectant booths aims to help the community, especially in the Kediri region which was affected by the spread of Covid-19. The masks and disinfectant booth products are carried out independently by the Kadiri University in collaboration with the students, lecturers, and alumni of Kadiri University, where the products will be submitted as a form of social service to people in need such as the traditional market in Grogol Village, Kediri Regency. In addition to distributing masks to the public, also given education through socialization the importance of doing a form of prevention of the spread of Covid-19 by always washing hands regularly, keep a distance, and always use a mask.